Edukasi dan Upaya Konseling Kristen bagi Remaja - Nehemia Nome; Sozanolo Zamasi; Sorimuda Sarumpaet; Linda Zenita Simanjuntak (Departement of Mathematics Education, 2023)
This research was conducted to examine mentoring efforts for people in the adolescent and adult groups. A group of people who have their variety and complexity understands and deal with problems with them. The reference used in the categorization of adolescent and adult groups is taken from the theory of Erik H Erikson. The researcher briefly explained the eight stages of Erik H Erikson's theory. But the focus of attention was on the group's Stage 5: Adolescence – Ages 12-18 and stage 6: Young Adulthood – Ages 19-40. This age group was chosen because generally in Indonesia it gives the name teenagers and youth. Erik H Erikson's grouping theory was chosen because it was accepted by many circles. Researchers use a descriptive qualitative approach by exploring the opinions of authors in their fields. Several opinions will be drawn in to get an idea of how counselors should assist these two age groups. The results found a careful effort if you want to go in and provide assistance to the youth-youth group. In that age group, a counselor is required to understand the psychology and labile attitudes that exist. This paper also proposes that churches, parents, and professional institutions pay special attention to adolescents and youth in the field of mentoring for those with problems.